Nesting behavior of Podium denticulatum Smith (Hymenoptera: Sphecidae) - Ribeiro,Favi (2010)
The nesting behavior of Podium denticulatum Smith was studied on the campus of Ribeirão Preto of the Universidade de São Paulo, SP, Brazil, from September 2003 to August 2005. The wasps established their nests in bamboo canes ranging from 11.4 cm to 26.2 cm in length and from 0.7 cm to 1.8 cm in internal diameter. Podium denticulatum nested almost exclusively in the hot and wet season (September-April), producing at least five generations per year. The cell provisioning was made with adult and nymphal cockroaches (Blattellidae) which were arranged venter-up and with the head inward toward the inner end of the cell. The construction of a temporary closure occurred in cells that took more than one day to be provisioned. The cells provisioned with a greater number of prey were more likely to produce females than males. The nests included 1-6 brood cells separated by mud partitions and arranged in a linear series. The innermost cells of the nests produced females, and the outermost cells produced males. Nests were parasitized by Eulophidae (Melittobia sp.), Chrysididae and Tachinidae.